Artificial fiber wound composite silicon-carbon negative electrode material as well as preparation method and application thereof

By recycling the PP separator of lithium-ion batteries, the carbon fibers are prepared and wound on the silicon carbon negative electrode material is solved, and the circulation performance of silicon carbon negative electrode material is limited by volume expansion is achieved, and the efficient circulation performance and rate performance is improved, while reducing costs.

CN119905550APending Publication Date: 2025-04-29WUHU ETC BATTERY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411925811.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing silicon-carbon anode materials have fallen off due to volume expansion during circulation, and the electrode sheets are cracked, which limits their cyclic performance and the cost of using graphene is higher.

Method used

Carbon fibers are prepared by recycling the PP separator of lithium-ion batteries, wrapped around the silicon-carbon negative electrode material, and artificial fibers are formed to wrap composite silicon-carbon negative electrode material to inhibit volume expansion and improve circulation performance.

Benefits of technology

It significantly improves the circulation performance and rate performance of lithium-ion batteries, reduces costs, and reduces dependence on conductive carbon black, and improves energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905550A_ABST
    Figure CN119905550A_ABST
Patent Text Reader

Abstract

The invention provides an artificial fiber wound composite silicon-carbon negative electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: 1) pretreating a PP diaphragm, and heating to a molten state to prepare fibers; 2) grinding and mixing the fiber obtained in the step 1) and a silicon-carbon negative electrode, and carbonizing to obtain a primary carbonized precursor; and 3) grinding the primarily carbonized precursor, and performing secondary carbonization to obtain the artificial fiber wound composite silicon-carbon negative electrode material. Compared with the prior art, the method utilizes a simple method to carbonize and recycle the PP diaphragm, prepare the carbon fiber, grind the carbon fiber to disorderly wind the silicon negative electrode and prepare the composite material, so that the conductivity and the cycle performance of the silicon negative electrode can be improved, and the problem of pole piece pulverization caused by volume expansion in the cycle performance of the silicon negative electrode is solved. And recycled materials are adopted for preparation, so that the cost is low. Meanwhile, the conductivity is improved, the use proportion of conductive carbon black in the formula is expected to be reduced, the content of active substances is increased, and the energy density of the formula system is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of battery materials, and in particular relates to an artificial fiber-wound composite silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, the field of lithium-ion batteries has developed rapidly. Faced with the growing demand for energy density, mature graphite anode materials can no longer meet the demand, and it is urgent to develop lithium-ion anode materials with higher energy density.

[0003] The third generation of silicon-carbon materials currently developed in the negative electrode market are known as the most promising negative electrode materials among many silicon-based materials due to their high energy density and higher initial efficiency than silicon-oxygen. However, the high volume expansion rate of silicon materials themselves causes the active materials to fall off the current collector in the later stages of the cycle, until the pole piece is cracked, thus limiting the cycle performance of silicon-carbon negative electrode materials.

[0004] The patent with the publication number CN 106898755 A published on June 27, 2017 discloses a method for preparing a silicon-carbon negative electrode material and a silicon-carbon negative electrode material prepared by the method. The disclosed preparation method includes: step 1, preparing a coating layer slurry containing graphene, spraying it into a coating chamber, and making the formed particles carry a charge, and the charge of each particle is Q1; step 2, spraying the core structure component into the coating chamber, and making its surface carry a charge opposite to that of the particles described in step 1, and the charge of each particle is Q2; step 3, coating reaction: adjusting the airflow in the coating chamber so that the particles in step 1 are uniformly coated on the surface of the core structure described in step 2; step 4, performing post-processing to obtain finished silicon-carbon particles; thereby preparing a silicon-carbon negative electrode material with excellent performance. However, it uses graphene, which is costly.

[0005] Therefore, it is very necessary to provide a silicon negative electrode material with excellent performance and lower cost. Summary of the invention

[0006] The purpose of the present invention is to provide a man-made fiber wound composite silicon-carbon negative electrode material and a preparation method thereof, and to use recycled diaphragms as raw materials to prepare carbon fiber wound silicon-carbon negative electrodes, thereby obtaining man-made fiber wound composite silicon-carbon negative electrode materials. The preparation method is simple, and the raw materials are recycled lithium-ion batteries. The raw materials are easily available and low in cost, and can be widely accepted by industrialization.

[0007] Another object of the present invention is to provide an application of a synthetic fiber wound composite silicon-carbon negative electrode material for lithium-ion batteries.

[0008] The specific technical solutions of the present invention are as follows:

[0009] A method for preparing a synthetic fiber wound composite silicon-carbon negative electrode material comprises the following steps:

[0010] 1) Pre-treating the PP diaphragm, heating it to a molten state, and making it into fibers;

[0011] 2) grinding and mixing the fiber obtained in step 1) and the silicon-carbon negative electrode, and carbonizing them to obtain a preliminary carbonized precursor;

[0012] 3) After grinding the primary carbonized precursor, secondary carbonization is performed to obtain an artificial fiber-wound composite silicon-carbon negative electrode material.

[0013] In step 1), the PP diaphragm refers to: a PP diaphragm recovered from a 40Ah battery cell for energy storage;

[0014] In step 1), the pretreatment refers to: at room temperature and pressure, immersing the PP membrane in dimethyl carbonate DMC for 5±0.5h, then immersing it in anhydrous ethanol for 5±0.5h, and taking it out and drying it in an oven at 80°C after the second immersion; the mass ratio of the PP membrane to DMC is 1:10; the mass ratio of the PP membrane to anhydrous ethanol is 1:20; through the above pretreatment, the effect of removing impurities is achieved, and preparation is made for subsequent melt spinning to obtain fibers, so as to prevent impurities from affecting the performance of the negative electrode after being made into fibers.

[0015] Furthermore, in step 1), the pretreated PP diaphragm is placed in the melt chamber of a spinning machine, melted into a molten state by heating, and then the molten polypropylene is extruded through a spinning disk to form fibers at the extrusion port, and the fibers are cooled to obtain sample fibers; the heating temperature is 180±5°C, the prepared fiber diameter is 50±5μm, and the fiber length is 3-5mm.

[0016] In step 2), the mass ratio of fiber to silicon-carbon negative electrode is 0.5-2:98-99.5;

[0017] In step 2), grinding and mixing, grinding by ball mill for 4.5-5.5h, so that the fibers are randomly wound on the silicon-carbon negative electrode;

[0018] In step 2), the carbonization refers to: heating up to 500°C at a heating rate of 0.5°C / min, keeping the temperature for 10h, to obtain a preliminary carbonized precursor;

[0019] In step 3), the sample after preliminary carbonization is ground again and placed in a tubular furnace in a pure argon state for secondary carbonization to form carbon fibers.

[0020] In step 3), the grinding refers to grinding in a ball mill for 4.5-5.5 hours; grinding and mixing again to further achieve fiber winding on the silicon-carbon negative electrode.

[0021] In step 3), the secondary carbonization is carried out by heating the temperature to 900° C. at a heating rate of 1° C. / min and keeping the temperature for 10 h.

[0022] The present invention provides an artificial fiber wound composite silicon-carbon negative electrode material, which is prepared by the above method.

[0023] The invention provides an application of a man-made fiber-wound composite silicon-carbon negative electrode material for preparing lithium-ion batteries.

[0024] The lithium-ion battery comprises a negative electrode, and the negative electrode slurry used in the negative electrode comprises a synthetic fiber wound composite silicon-carbon negative electrode material, conductive carbon black and sodium alginate; the mass ratio is 80-95:2.5-10:2.5-10.

[0025] The present invention uses the PP diaphragm recycled from the dismantling of the 40Ah battery cell for energy storage as the raw material. After the recycled diaphragm is processed, carbon fiber is prepared. The carbon fiber is compounded with the silicon-carbon negative electrode to form a composite material. The carbon fiber has high conductivity and slender physical properties. It is wound on the surface of the silicon-carbon negative electrode to inhibit its volume expansion and improve the cycle performance. The present invention uses lithium-ion battery recycling technology to make carbon fiber wound on the surface of the silicon-carbon negative electrode to improve the cycle performance of the capacity battery.

[0026] Compared with the prior art, the present invention uses a simple method to carbonize and recycle PP diaphragms to prepare carbon fibers. The carbon fibers are ground and randomly wound around silicon negative electrodes to prepare composite materials, which can improve the conductivity and cycle performance of silicon negative electrodes and improve the problem of pole piece pulverization caused by volume expansion in the cycle performance of silicon negative electrodes. And it is prepared using recycled materials at a low cost. At the same time, the conductivity is improved, which is expected to reduce the proportion of conductive carbon black used in the formula, increase the content of active substances, and improve the energy density of the formula system. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the EIS data diagram of each embodiment and comparative example;

[0028] Figure 2 It is a charging rate data diagram of each embodiment and comparative example. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The test materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The silicon-carbon negative electrodes used in the present invention are all commercially available products, and the silicon-carbon negative electrodes used in the examples and comparative examples are the same.

[0031] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0032] Example 1

[0033] Use synthetic fiber wound composite silicon-carbon negative electrode material with a mass ratio of 1:99; use pure lithium sheet and silicon-carbon negative electrode sheet with a mass ratio of 80% to make a semi-electric button cell, control humidity throughout the production process, and finally do cycle test and rate test. The details are as follows:

[0034] A method for preparing a synthetic fiber wound composite silicon-carbon negative electrode material comprises the following steps:

[0035] 1) Dismantle the waste lithium-ion battery, take out the recycled PP diaphragm, soak the diaphragm in DMC liquid for 5 hours, and then soak it in ethanol for 5 hours, wherein the mass ratio of PP diaphragm to DMC is 1:10; the mass ratio of PP diaphragm to anhydrous ethanol is 1:20, and after soaking, take it out and dry it in an oven at 80°C; put the treated PP diaphragm into the melt chamber of the spinning machine, heat it to 180°C, melt it into a molten state, and then extrude the molten polypropylene through a spinning disk, and form fibers at the extrusion port, and obtain fibers after the fibers are cooled; the prepared fibers have a diameter of 50±5μm and a length of 3-5mm.

[0036] 2) Weigh a certain amount of fiber and silicon-carbon negative electrode, with a mass ratio of fiber to silicon-carbon material of 1:99, place them in a ball mill for 5 hours to mix, and then place them in a tubular furnace in an argon state, with a heating rate of 0.5°C / min, and the temperature is raised to 500°C, and the holding time is 10 hours to obtain a preliminary carbonized precursor;

[0037] 3) The preliminary carbonized precursor was placed in a ball mill and ground for 5 hours to mix, and then placed in a tubular furnace in an argon state for secondary carbonization. The heating rate was 1°C / min, and the temperature was raised to 900°C for 10 hours to obtain the carbon fiber composite silicon-carbon negative electrode material B for battery cell preparation.

[0038] The production process of semi-electric button cells is as follows:

[0039] S1. Add 80% carbon fiber composite silicon-carbon negative electrode material B, 10% conductive carbon black, and 10% sodium alginate into a stirring tank, and stir at high speed to prepare a negative electrode slurry;

[0040] S2. Coat the negative electrode slurry described in step S1 on a 6 μm copper foil, and then bake at 110±5° C., roll-press, and cut into pieces to form negative electrode sheets.

[0041] S3, prepare pure lithium sheets, springs, gaskets, diaphragms, and battery shells to make semi-electric buckle batteries.

[0042] S4, take 3ea parallel samples to do 0.1C / 0.1C cycle test, cycle 200 times, and observe the specific capacity attenuation; take 3ea parallel samples to do EIS test after full charge; finally take 3ea parallel samples to do rate charge and discharge test after full charge;

[0043] Example 2

[0044] The composite silicon-carbon negative electrode material wound with artificial fiber at a mass ratio of 0.5:99.5 uses pure lithium sheets and 80% silicon-carbon negative electrode sheets to make a semi-electric button cell. The humidity is controlled during the production process, and finally the cycle test and rate test are performed. The details are as follows:

[0045] A method for preparing a synthetic fiber wound composite silicon-carbon negative electrode material comprises the following steps:

[0046] 1) Dismantle the waste lithium-ion battery, take out the recycled PP diaphragm, soak the diaphragm in DMC liquid for 5 hours, and then soak it in ethanol for 5 hours, the mass ratio of PP diaphragm to DMC is 1:10; the mass ratio of PP diaphragm to anhydrous ethanol is 1:20, take out and dry in an oven at 80°C after soaking; put the treated PP diaphragm into the melt chamber of the spinning machine, heat it to 180°C, melt it into a molten state, and then extrude the molten polypropylene through the spinning disk, and form fibers at the extrusion port, and obtain sample fibers after the fibers are cooled; the prepared fibers have a diameter of 50±5μm and a length of 3-5mm;

[0047] 2) Weigh a certain amount of fiber sample and silicon-carbon negative electrode, with a mass ratio of fiber to silicon-carbon material of 0.5:99.5, grind in a ball mill for 5 h, put into a tubular furnace in an argon state, heat up at a rate of 0.5 °C / min to 500 °C, and keep warm for 10 h to obtain a preliminary carbonized precursor;

[0048] 3) The preliminary carbonized precursor was placed in a ball mill for grinding for 5 hours and then placed in a tubular furnace in an argon state for secondary carbonization. The temperature was raised to 900°C at a heating rate of 1°C / min and kept at this temperature for 10 hours to obtain a carbon fiber composite silicon-carbon negative electrode material C for battery cell preparation.

[0049] The production process of semi-electric button batteries is as follows:

[0050] S1. Add 80% carbon fiber composite silicon-carbon negative electrode material C, 10% conductive carbon black, and 10% sodium alginate into a stirring tank, and stir at high speed to prepare a negative electrode slurry;

[0051] S2. Coat the negative electrode slurry described in step S1 on a 6um copper foil, then bake at 110±5°C, roll-press, and cut into pieces to make negative electrode sheets.

[0052] S3, prepare pure lithium sheets, springs, gaskets, diaphragms, and battery shells to make semi-electric buckle batteries.

[0053] S4. Take 3ea parallel samples to perform 0.1C / 0.1C cycle test, cycle 200 times, and observe the specific capacity attenuation; then take 3ea parallel samples and fully charge them to perform EIS test; finally, take 3ea parallel samples and fully charge them to perform rate charge and discharge test.

[0054] Example 3

[0055] Use synthetic fiber wound composite silicon-carbon negative electrode material with a mass ratio of 2:98, use pure lithium sheet and silicon-carbon negative electrode sheet with a mass ratio of 80%, make a semi-electric button cell, control humidity throughout the production process, and finally do cycle test and rate test. The specific process is as follows:

[0056] A method for preparing a synthetic fiber wound composite silicon-carbon negative electrode material comprises the following steps:

[0057] 1) Disassemble a 40Ah waste lithium-ion battery, take out the recycled PP diaphragm, soak the diaphragm in DMC liquid for 5 hours, and then soak it in ethanol for 5 hours, wherein the mass ratio of PP diaphragm to DMC is 1:10; the mass ratio of PP diaphragm to anhydrous ethanol is 1:20; after soaking, take it out and dry it in an oven at 80°C; put the treated PP diaphragm into the melt chamber of a spinning machine, heat it to 180°C, melt it into a molten state, and then extrude the molten polypropylene through a spinning disk, and form fibers at the extrusion port, and obtain sample fibers after the fibers are cooled, and the prepared fibers have a diameter of 50±5μm and a length of 3-5mm;

[0058] 2) Weighing the fibers and silicon-carbon negative electrode prepared in step 1), with a mass ratio of fibers to silicon-carbon materials of 2:98, grinding them in a ball mill for 5 h, and then placing them in a tubular furnace in an argon state, heating them at a rate of 0.5 °C / min to a temperature of 500 °C, and keeping them at this temperature for 10 h to obtain a preliminary carbonized precursor;

[0059] 3) The preliminary carbonized precursor was placed in a ball mill and ground for 5 hours to mix, and then placed in a tubular furnace in an argon state for secondary carbonization. The heating rate was 1°C / min, and the temperature was raised to a heating temperature of 900°C for 10 hours to obtain a carbon fiber composite silicon-carbon negative electrode material A for battery cell preparation.

[0060] The production process of semi-electric button cells is as follows:

[0061] S1. Add 80% carbon fiber composite silicon-carbon negative electrode material A, 10% conductive carbon black, and 10% sodium alginate in a stirring tank, and stir to form a negative electrode slurry;

[0062] S2. Coat the negative electrode slurry described in step S1 on a 6 μm copper foil, and then bake at 110±5° C., roll-press, and cut into pieces to form negative electrode sheets.

[0063] S3, prepare pure lithium sheets, springs, gaskets, diaphragms, and battery shells to make semi-electric buckle batteries.

[0064] S4. Take 3ea parallel samples to perform 0.1C / 0.1C cycle test, cycle 200 times, and observe the specific capacity attenuation; then take 3ea parallel samples and fully charge them to perform EIS test; finally, take 3ea parallel samples and fully charge them to perform rate charge and discharge test.

[0065] Comparative Example 1

[0066] A semi-electric button cell was made by using a pure lithium sheet and a silicon-carbon negative electrode sheet with a mass ratio of 80%. The humidity was controlled during the whole process, and finally a cycle test and a rate test were performed. The raw material silicon-carbon negative electrode used in Example 3 was used as the negative electrode active material.

[0067] The production process of semi-electric button batteries is as follows:

[0068] S1. Add 80% raw material silicon-carbon negative electrode, 10% conductive carbon black, 10% sodium alginate, etc. in a mass ratio into a stirring tank and stir at high speed to form a negative electrode slurry;

[0069] S2. Coat the negative electrode slurry described in step 1 on a 6 μm copper foil, then bake at 110±5° C., roll-press, and cut into pieces to make negative electrode sheets.

[0070] S3, prepare pure lithium sheets, springs, gaskets, diaphragms, and battery shells to make semi-electric buckle batteries.

[0071] S4, take 3ea parallel samples to do 0.1C / 0.1C cycle test, cycle 200 times, and observe the specific capacity attenuation; take 3ea parallel samples to do EIS test after full charge; finally take 3ea parallel samples to do rate charge and discharge test after full charge;

[0072] Example 4

[0073] The composite silicon-carbon negative electrode material with a mass ratio of 2:98 is wound with artificial fibers. Pure lithium sheets and silicon-carbon negative electrode sheets with a mass ratio of 95% are used to make semi-electric button cells. The humidity is controlled during the production process, and finally cycle tests and rate tests are performed. The details are as follows:

[0074] A method for preparing a synthetic fiber wound composite silicon-carbon negative electrode material comprises the following steps:

[0075] According to Example 3, the composite silicon-carbon negative electrode material was wound with artificial fibers in a mass ratio of 2:98 to obtain a carbon fiber composite silicon-carbon negative electrode material A, and a battery cell was prepared.

[0076] The production process of semi-electric button batteries is as follows:

[0077] S1. Add 95% carbon fiber composite silicon-carbon negative electrode material A, 2.5% conductive carbon black, 2.5% sodium alginate, etc. into a stirring tank and stir at high speed to prepare a negative electrode slurry;

[0078] S2. Coat the negative electrode slurry described in step S1 on a 6 μm copper foil, and then bake at 110±5° C., roll-press, and cut into pieces to form negative electrode sheets.

[0079] S3, prepare pure lithium sheets, springs, gaskets, diaphragms, and battery shells to make semi-electric buckle batteries.

[0080] S4. Take 3ea parallel samples to perform 0.1C / 0.1C cycle test, cycle 200 times, and observe the specific capacity attenuation; then take 3ea parallel samples and fully charge them to perform EIS test; finally, take 3ea parallel samples and fully charge them to perform rate charge and discharge test.

[0081] according to Figure 1 and Figure 2 It can be seen that the artificial fiber-wound composite silicon-carbon negative electrode material prepared by the present invention with a mass ratio of recycled fiber to silicon-carbon negative electrode of 0.5-2:98-99.5 can significantly improve the performance of the battery compared to the silicon-carbon negative electrode without fiber winding. And under the condition that the amount of carbon black used is only 2.5%, it still has high performance and can reduce costs.

[0082] In the present invention, the carbon fiber winding effect mainly inhibits the volume expansion of the silicon negative electrode material and improves the cycle performance of the battery core; the high conductivity of the carbon fiber increases the conductivity of the silicon-carbon negative electrode and improves the rate performance of the battery core; it is expected to reduce the proportion of conductive carbon black used in the formula, increase the content of active substances, and improve the energy density of the formula system. The recycled PP diaphragm is used as the raw material, which is low in cost and creates technical support for the field of lithium-ion battery recycling.

[0083] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a synthetic fiber wound composite silicon-carbon negative electrode material, characterized in that: The preparation method comprises the following steps: 1) Pre-treating the PP diaphragm, heating it to a molten state, and making it into fibers; 2) grinding and mixing the fiber obtained in step 1) and the silicon-carbon negative electrode, and carbonizing them to obtain a preliminary carbonized precursor; 3) After grinding the primary carbonized precursor, secondary carbonization is performed to obtain an artificial fiber-wound composite silicon-carbon negative electrode material.

2. The preparation method according to claim 1, characterized in that: In step 1), the pretreatment refers to: at room temperature and pressure, immersing the PP membrane in dimethyl carbonate DMC for 5±0.5h, then immersing it in anhydrous ethanol for 5±0.5h, and after the second immersion, taking it out and drying it in an oven at 80°C.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the PP membrane to DMC is 1:10; the mass ratio of the PP membrane to anhydrous ethanol is 1:

20.

4. The preparation method according to claim 1, characterized in that: In step 1), the diameter of the prepared fiber is 50±5 μm and the length of the fiber is 3-5 mm.

5. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of fiber to silicon-carbon negative electrode is 0.5-2:98-99.

5.

6. The preparation method according to claim 1 or 5, characterized in that: In step 2), the carbonization refers to: heating to 500° C. and keeping the temperature for 10 hours to obtain a preliminary carbonized precursor.

7. The preparation method according to claim 1, characterized in that: In step 3), the secondary carbonization is carried out by heating the temperature to 900° C. at a heating rate of 1° C. / min and keeping the temperature for 10 h.

8. The preparation method according to claim 1, characterized in that: In step 2) and step 3), the grinding refers to grinding in a ball mill for 4.5-5.5 hours.

9. A synthetic fiber wound composite silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the artificial fiber wound composite silicon-carbon negative electrode material according to claim 9, characterized in that: Used in lithium-ion battery preparation.

Citation Information

Patent Citations

  • Silicon-carbon cathode material and method for preparing same

    CN106898755A